On the ultimate tensile strength of tantalum. (March 2017) - Hahn, Eric N.; Germann, Timothy C.; Ravelo, Ramon; Hammerberg, James E.; Meyers, Marc A.
Abstract: Strain rate, temperature, and microstructure play a significant role in the mechanical response of materials. Using non-equilibrium molecular dynamics simulations, we characterize the ductile tensile failure of a model body-centered cubic metal, tantalum, over six orders of magnitude in strain rate. Molecular dynamics calculations combined with reported experimental measurements show power-law kinetic relationships that vary as a function of dominant defect mechanism and grain size. The maximum sustained tensile stress, or spall strength, increases with increasing strain rate, before ultimately saturating at ultra-high strain rates, i.e. those approaching or exceeding the Debye frequency. The upper limit of tensile strength can be well estimated by the cohesive energy, or the energy required to separate atoms from one another. At strain rates below the Debye frequency, the spall strength of nanocrystalline Ta is less than single crystalline tantalum. This occurs in part due to the decreased flow stress of the grain boundaries; stress concentrations at grain boundaries that arise due to compatibility requirements; and the growing fraction of grain-boundary atoms as grain size is decreased into the nanocrystalline regime. In the present cases, voids nucleate at defect structures present in the microstructure. The exact makeup and distribution of defects is controlled by the initial microstructure and the plastic deformation during both compression and expansion, where grain boundaries and grain orientation play critical roles. Graphical abstract: Image 1